2015
DOI: 10.3892/etm.2015.2656
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of p16 and RASSF1A genes may contribute to the risk of papillary thyroid cancer: A meta-analysis

Abstract: The aim of the present meta-analysis was to investigate the correlation of promoter methylation of the p16 and Ras association domain family 1 isoform A (RASSF1A) genes with the risk of the development of papillary thyroid cancer (PTC). A number of electronic databases were searched without language restrictions as follows: Medline (1966-2013), the Cochrane Library database (Issue 12, 2013), Embase (1980-2013), CINAHL (1982-2013), Web of Science (1945-2013) and the Chinese Biomedical Database (CBM; 1982-2013).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…The hypermethylation of TSG promoter suppresses genes expression by inhibiting transcription, thereby affecting cell signaling pathways. Two previous meta-analyses demonstrated the association between RASSF1A promoter methylation and PTC risk [ 31 , 41 ]. In the current report, a comprehensive review was carried out to determine the relationship between thyroid cancer susceptibility and gene methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypermethylation of TSG promoter suppresses genes expression by inhibiting transcription, thereby affecting cell signaling pathways. Two previous meta-analyses demonstrated the association between RASSF1A promoter methylation and PTC risk [ 31 , 41 ]. In the current report, a comprehensive review was carried out to determine the relationship between thyroid cancer susceptibility and gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, RASSF1 promoter inactivation has been detected in more than 30% of thyroid tumors, representing the most and frequent event in thyroid cancers [ 72 , 73 ]; however, in some reports, no significant correlation between RASSF1 methylation and thyroid cancer risk was detected [ 68 , 74 – 78 ]. In two prior meta-analyses, researchers only examined the association between RASSF1 promoter methylation and PTC risk [ 31 , 41 ]. Although the results of these prior meta-analyses demonstrated that the frequency of RASSF1 promoter methylation was significantly associated with increased risk of thyroid cancer, our study showed that the influence of RASSF1 promoter methylation was lower than those of CDH1 and SLC5A8 promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to conduct a meta-analysis to determine the strength of association between RASSF1A promoter methylation and thyroid cancer. In the literature retrieval, a previous meta-analysis was found 45. However, the meta-analysis only explored the association between RASSF1A promoter methylation and PTC risk, and no clinical information was included.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated RASSF1A methylation differed in PTC compared with normal thyroid and was correlated with extracapsular invasion inversely. It suggested that RASSF1A has a potential role as a molecular marker for characterization of PTC histopathology [11][12][13][14][15]. It is shown that hypermethylation of RASSF1A promoter region is 20-32% in PTC.…”
Section: Ras Association Domain Family 1 (Rassf1a)mentioning
confidence: 99%